STATE-OWNED ENTERPRISES AND PRIVATIZATION «BY NEW» - Riabova Kateryna О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article is devoted to the analysis of the privalisation processes into Ukraine and the legal status of state-owned enterprises. Methods of research: the legal basis that regulates relations connected with the state-owned enterprises, as well the legal status of foreign state-owned enterprises, is analyzed. Results: the need to save state enterprises of the nagging branches of the economy from thoughtless privatization. Discussion: regulatory and regulatory issues that arise when implementing the new privatisational proceduress.